2010
DOI: 10.1088/0964-1726/19/10/105025
|View full text |Cite
|
Sign up to set email alerts
|

Repair of a delaminated plate under static loading with piezoelectric patches

Abstract: Repair of a delaminated plate under a static loading with piezoelectric patches is developed through a numerical model and the finite element method (FEM). Tensile and compressive forces distributed on the upper and lower layers of the delamination, which would lead to a shear stress singularity and the corresponding second fracture mode on the delamination edges, are solved by the numerical model. In order to repair the delaminated plate by eliminating the tensile and compressive forces along the edges of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…An investigative work by Wu et al [52] substantiated the degree to which the piezoelectric based repair techniques are significant when it comes to the patches' application in delaminated plates. The plates were explored both analytically and through an FEM model when they were subjected to a static transverse load.…”
Section: Active Repair Of Composite Structuresmentioning
confidence: 99%
“…An investigative work by Wu et al [52] substantiated the degree to which the piezoelectric based repair techniques are significant when it comes to the patches' application in delaminated plates. The plates were explored both analytically and through an FEM model when they were subjected to a static transverse load.…”
Section: Active Repair Of Composite Structuresmentioning
confidence: 99%
“…The research results indicated that the variation of the slope of continuity at the crack position for simply supported beam subjected to bending moment can be removed by applying an appropriate voltage to the piezoelectric layer. Similarly, Wu and Wang's exploratory study (Wu and Wang, 2010) authenticated the standard degree at which the piezoelectric-based repair methods are significant, especially when the patches' application in delaminated plates is involved. These plates, subjected to static transverse load, were investigated using both analytical and finite element method (FEM) model.…”
Section: Introductionmentioning
confidence: 96%
“…In this work, piezoelectric patches have used to induce local moments for the compensation of decreased buckling capacity. Finite element method is used to study the repair of a delaminated plate by piezoelectric patches under static loading (Wu and Wang, 2010a). The dependence of the size and location of the delamination area on the voltages applied to the discrete electrodes is discovered in this work.…”
Section: Introductionmentioning
confidence: 99%